2023
DOI: 10.11646/phytotaxa.589.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Marasmius margallensis, a new species of Marasmius sect. Sicci from Margalla Hills, Pakistan

Abstract: Marasmius margallensis sp. nov. of sect. Sicci from Margalla hills, Islamabad, Pakistan, is described and illustrated, based on morphological characteristics and multigene phylogenetic analyses. The taxon is characterized by a pale yellow to dull orange pileus with light gray margins, clavate to narrowly fusiform basidiospores, rather short pleurocystidia and hymeniderm pileipellis with Siccus-type broom-cells. Marasmius pulcherripes is closest relative of the newly described species M. margallensis in sect. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…From Pakistan work was done on this Genus and new to science and a new Pakistan species was reported identified and described. Marasmius margallensis, Marasmius oreades, reported by Razzaq and Khalid (2023) and Razaq et al (2013) reported the noval species from the genus. Aman et al (2022) published "A compendium of macrofungi from Pakistan" described species from the Genus.…”
Section: Introductionmentioning
confidence: 98%
“…From Pakistan work was done on this Genus and new to science and a new Pakistan species was reported identified and described. Marasmius margallensis, Marasmius oreades, reported by Razzaq and Khalid (2023) and Razaq et al (2013) reported the noval species from the genus. Aman et al (2022) published "A compendium of macrofungi from Pakistan" described species from the Genus.…”
Section: Introductionmentioning
confidence: 98%